Calorific Value and Chemical Composition of Five Semi-Arid Mexican Tree Species - Ngangyo Heya, Maginot; Foroughbakhch Pournavab, Rahim; Carrillo Parra, Artemio; Rutiaga Quiñones, José Guadalupe; Zelinski, Volker; Pintor Ibarra, Luis (2016)
The current global energy crisis has generated growing interest in looking for alternatives to traditional fossil fuels, presenting lignocellulosic materials as a promising resource for sustainable energy production. In this paper, the calorific values and chemical composition of the trunks, branches, twigs and leaves of five timber species of the semi-arid land of Mexico (Helietta parvifolia (Gray) Benth., Ebenopsis ebano (Berl.) Barneby, Acacia berlandieri (Benth.), Havardia pallens (Benth.) Britton & Rose and Acacia wrightii (Benth.)) were determined according to international standards. The results highlighted the calorific value ranges of 17.56 to 18.61 MJ kg´1 in trunks, 17.15 to 18.45 MJ kg´1 in branches, 17.29 to 17.92 MJ kg´1 in twigs, and 17.35to 19.36 MJ kg´1 in leaves. The pH presented an acidic trend (3.95–5.64). The content of mineral elements varied in trunks (1.09%–2.29%), branches (0.86%–2.75%), twigs (4.26%–6.76%) and leaves (5.77%–11.79%), showing the higher proportion in Ca (57.03%–95.53%), followed by K (0.95%–19.21%) and Mg (0.88%–13.47%). The highest amount of extractives was obtained in the methanolic solvent (3.96%–17.03%). The lignin recorded values of 28.78%–35.84% for trunks, 17.14%–31.39% for branches and 20.61%–29.92% for twigs. Lignin showed a moderately strong correlation (r = 0.66) with calorific value, but the best mathematical model was registered with the calorific value depending on the pH and lignin (R 2 = 58.86%).